TRADITIONAL INDONESIAN GASTRONOMY AS A CULTURAL TOURISM ATTRACTION - Amiluhur Soeroso; Y. Sri Susilo (MESP–FEB UNS, 2014)
Culture is the characteristics of a particular group of people, defined by everything from language, religion, cuisine, social habits, music and arts. As a part of the culture, cuisine and gastronomy significantly related to tourism. It has always been a component of the culinary tourist experiences. Tourist is not only eating to avoid falling ill, but also they want to understand a region or a country. Of food, they can receive information about a population and its civilization. Aims of the study is to assess whether travelers only want to see the temples, artifacts, sites etc., or they just want to feel another very memorable experience while visiting tourism objects in Indonesia, including sample cuisine and regional specialties. Then, the author wants to see the drivers for rebuild the character of gastronomy and traditional Indonesian food as a tourism attraction. Therefore, the author also desires to convey that the preservation of the traditional gastronomy, as a part of the national culture, is very important for the development of cultural tourism attraction. This study uses survey techniques to collect primary and secondary data. Researcher conducted indepth interviews with 150 tourists who are visiting to tourism object in Indonesia. And then, the researcher sent a questionnaire by email to 150 tourism stakeholders, especially those working in the field of gastronomy. Results of this study showed that tourists want others exotic tourism experiences. Travelers will make food as part of the experience when travel to tourism object in Indonesia. There are eight trends that could encourage gastronomy as cultural tourism attraction i.e. trading up, multiculturalism, media communication, demographics and household change, communities’ involvement, glocalization (globalization with local flavor), product quality, and ecofriendly product. Beside that, need to protect against the diversity of local food, and improve the image of the non-rice food equivalent to the rice food. Thus, communities should be given the knowledge of food quality in the surrounding areas and the implementation of